Peran Guru dalam Pembelajaran Bahasa Arab di MA Palapa Nusantara NW Selebung Lombok - Raudatussolihah, Baiq; Jamal, Mardhiana; Fathurrahman, Ali (Fakultas Teknik Universitas Negeri Makassar, 2025)
This study aims to describe and analyze the role of teachers in Arabic language learning at MA Palapa Nusantara NW Selebung Lombok. The role of teachers is very crucial in creating an effective, efficient and enjoyable learning process, especially in the context of Arabic language learning. This study uses a qualitative approach with a case study method, where data is collected through observation, in-depth interviews, and documentation. The results of the study indicate that teachers play various strategic roles, namely as learning planners, facilitators, motivators, and evaluators. Teachers also play a role in developing contextual learning strategies that are appropriate to local conditions and student characteristics. Despite limited facilities and infrastructure, teachers continue to strive to innovate in teaching Arabic through the use of simple media and communicative approaches. These findings emphasize the importance of improving pedagogical competence and teacher professionalism in order to improve the quality of Arabic language learning. This study provides implications for policies to improve teacher quality and develop local-based curricula that support optimal Arabic language learning.